Factors Affecting the Distribution of Micro, Small and Medium Enterprises (MSME) Financing in Islamic Banks - Annisa Masruri Zaimsyah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose:This study aims to analyses of the influence of the external and internal factors on medium and small micro Enterprise financing in Indonesia Islamic Bank exsternal factors consist of inflation, BI Rate and Exceng Rate, while the internal factors consists of ROA, CAR, BOPO, FDR and NPF. Design/Method/Approach: The analysis technique used in this study is multiple regression with OLS approach. The data used this study are monthly data from 2014-2018. Data obtained from OJK and Bank Indonesia reports.Findings: The finding results of this study, change in macroeconomic conditions (external factor) will indirectly have an impact on the internal conditions od Islamic Bank and will have an impact on intermediation function, especially for the MSME sector, while partially the factors that influence MSME financing are only in inflation and Exceng rates, CAR, BOPO, NPF. FDR and BI Rate does not affect MSME financing because Islamic Bank do not use the interest system but instead use the profit sharing system.Originality/Values: The main contribution of this study to industry platetrs, Islamic bank and policy makers. Islamic bank must make more efferts to provide financing for MSME. Islamic Banks must be innovative and creative in creating and offering new products related to financing to MSME.